Description of the application of Watermelon of Juice Administration to Reduce Blood Pressure in Patients Suffering from Hypertension - Yeni Warni Sari; Sukmana, Mayusef; Fanny Metungku; Sholichin, Sholichin (Mulawarman Nursing Indonesia Journal, 2025)
Background: Hypertension is a long-term disease, this disease makes the heart work harder to pump blood through the body's blood arteries which causes heart disease. This can cause damage to blood vessels. Hypertension is characterized by a person's blood pressure being higher than normal and with symptoms such as dizziness, headaches, migraines, irritability, nosebleeds, stiff neck, dizzy eyes, insomnia, and blood pressure results of more than 120/80 mmHg. Method: The research design uses a descriptive research design with a case study approach. by measuring blood pressure using a tensiometer and the results obtained through blood pressure examination and after consuming 200 grams of watermelon juice. Results:. The application of watermelon juice administration found that there was a change in blood pressure in hypertension patients before and after the application of watermelon juice administration in hypertension patients with a decrease in blood pressure in three participants Conclusions: There was a change in blood pressure between before and after administration of processed watermelon juice to reduce blood pressure in hypertension sufferers in the three participants